Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) Methods of Exclusive Matte Lip Cream - Fitriana Eka Setyaningrum (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2020)
Now cosmetics become one of the current human needs and increasingly develop or become a trend in society. One of the decorative cosmetics for lips is Lip Cream. PT produces exclusive Matte Lip Cream. Paragon Technology and Innovation, but many cosmetics competitors appear lately, and some complaints about the product. This research aims to analyze customer satisfaction and analyze the important attributes of Exclusive Matte Lip Cream. The sampling method used is Simple Random Sampling and analyzed by using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The results of customer satisfaction are 75.89%, which means that customers are satisfied. The attribute that needs to be fixed is Formula & Texture of the new formulated Exclusive Matte Lip Cream, especially for lip cream density.